COMPARATIVE ANALYSIS OF HEALTH IN URBAN AND VILLAGE ADOLESCENTS IN BELGOROD REGION - T.A. Romanova; V.I. Akin'shin ("Paediatrician" Publishers LLC, 2008)
The data on level and structure of morbidity in adolescents, depending on place of living, social history of their families, age and sex was presented in this article. This data was obtained from results of preventive examination in younger and older adolescents. Authors of trial suggest varied approach to growth and development observation of adolescents, depending on place of their living.Key words: adolescents, morbidity, aboriginal population, migrants.